#3: Periviable Birth. Issue 4 (December 2016) - Ecker, J.L.; Kaimal, A.; Mercer, B.M.; Blackwell, S.C.; deRegnier, R.A.; Farrell, R.M.; Grobman, W.A.; Resnik, J.L.; Sciscione, A.C.
Abstract : ( Am J Obstet Gynecol 2015;213(5):604–614) This consensus statement describes newborn outcomes after periviable birth (delivery occurring from 20 0/7 weeks to 25 6/7 weeks of gestation), provides current evidence and recommendations regarding interventions in cases where delivery is anticipated near the limit of viability, and provides an outline for family counseling with the goal of incorporating informed patient preferences. It is reported that approximately 0.5% of all births occur before the third trimester of pregnancy and these very early deliveries result in the majority of neonatal deaths and >40% of infant deaths. The consensus statement intends to provide support and guidance regarding decisions (declining or accepting interventions and therapies) based on individual circumstances and patient values.